2018
DOI: 10.2516/ogst/2018076
|View full text |Cite
|
Sign up to set email alerts
|

A model of wax deposition under oil-gas two-phase stratified flow in horizontal pipe

Abstract: A model of wax deposition based on molecular diffusion mechanism, for oil-gas two-phase stratified pipe flow is developed. In the model, unidirectional fully developed flow analyses of momentum, heat and mass transfer are presented. And, a cube cage model is used to describe the wax deposit structure considering the effect of oil flow shear on the deposit. Calculation of wax deposit is compared well with a flow loop experiment. In particular, the model could give the wax deposit forming a crescent shape at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…It can be seen from Figure 10 that, the crystal structure of Akshabulak oil at 5°C without EVA is much larger than crystal structures of oil when we applied EVA and EVA-M. Moreover, Akshabulak oil at 5°C easily solidified without adding any additives due to formation of various shapes of wax depositions [25,26]. According to studies the morphology of the crystal structures of paraffins after the addition of modified EVA it should be concluded that the formation of plate-like structures is due to repellent of wax crystals by the polar acetate group in EVA copolymer that prevent the formation of large agglomerates of Table 7.…”
Section: Influence Of Modified Ppd On Transition Of Waxy Crude Oils Fmentioning
confidence: 96%
“…It can be seen from Figure 10 that, the crystal structure of Akshabulak oil at 5°C without EVA is much larger than crystal structures of oil when we applied EVA and EVA-M. Moreover, Akshabulak oil at 5°C easily solidified without adding any additives due to formation of various shapes of wax depositions [25,26]. According to studies the morphology of the crystal structures of paraffins after the addition of modified EVA it should be concluded that the formation of plate-like structures is due to repellent of wax crystals by the polar acetate group in EVA copolymer that prevent the formation of large agglomerates of Table 7.…”
Section: Influence Of Modified Ppd On Transition Of Waxy Crude Oils Fmentioning
confidence: 96%
“…According to the operating conditions (pressure, temperature, liquid and gas superficial velocities, pipe orientation, and fluid properties) [2], both phases will be distributed in a certain topology called flow pattern. The knowledge of the latter is required for a better estimation of the hydrodynamics, thermal properties [3], choice of models closures in transient multiphase flow simulation codes [4,5], as well as for the modeling of flow assurance phenomena such as wax deposition [6].…”
Section: Introductionmentioning
confidence: 99%
“…Duan et al [53] proposed a model for wax deposition in oilgas two-phase stratified flow in horizontal pipe. The geometry considered is three-dimensional.…”
Section: Introductionmentioning
confidence: 99%